Arrhythmia mechanism dependent pulmonary vein ablation in paroxysmal atrial fibrillation - Gottlieb, Lisa A.; Dekker, Lukas R. C.; Coronel, Ruben (Frontiers in Physiology, 2023)
Atrial fibrillation (AF) often requires invasive treatment by ablation to decrease symptom burden. The pulmonary veins (PV) are thought to trigger paroxysms of AF, and ablative PV isolation (PVI) is a cornerstone in AF treatment. However, incomplete PVI, where electrical conduction between the PV and left atrium (LA) is maintained, is curative of AF in a subset of patients. This implies that an antiarrhythmic effect other than electrical isolation between the PV and LA plays a role in AF prevention in these patients. We reason that the PV myocardium constitutes an arrhythmogenic substrate conducive to reentry in the patients with curative incomplete PVI. This PV substrate is amenable to ablation, even when conduction between the LA and PV persists. We propose that PV ablation strategies are differentiated to fit the arrhythmogenic mechanisms in the individual patient. PV substrate modification in patients with PV reentry may constitute a new therapeutic approach that is potentially simpler and more effective, in this subgroup of patients.